How Work-Life Balance Factors and Employee Performance are Systematically Reviewed Based on Moderation and Mediation Factors in the Digital and Hybrid Work Era? Bagaimana Faktor Keseimbangan Kerja-Kehidupan dan Kinerja Karyawan Dievaluasi Secara Sistematis Berdasarkan Faktor Moderasi dan Mediasi dalam Era Kerja Digital dan Hybrid? - Ahmad Fauzan Fadlan; Sukirman; Syafaat Nuryadi; Nandan Limakrisna (Universitas Muhammadiyah Sidoarjo, 2025)
This study aims to conduct a systematic review of the relationship between Work-Life Balance (WLB) and employee performance (EP), and to identify factors that moderate and mediate the relationship in the context of the digital and hybrid work era. The review was conducted by analyzing research literature from 2018-2024 published in the Scopus scientific journal. Inclusion criteria include studies that examine the relationship between WLB and EP, as well as the factors that influence the relationship. Exclusion criteria include studies that are not relevant to the digital and hybrid work context. Furthermore, article selection was carried out using the PRISMA approach and content analysis to extract key findings. The results of the review indicate that WLB has a positive relationship with EP, with several factors that moderate and mediate the relationship. Psychological well-being mediates the relationship between WLB and EP, while factors such as organizational support, workload, work flexibility, and technostress moderate this relationship. The theoretical implications of these findings are that they can broaden the understanding of the mechanisms that link WLB and EP in the digital and hybrid work era. Meanwhile, the practical implications of these findings can provide guidance for organizations in determining policies both in practice in human resource management (HRM) in an organization that supports employee WLB, so as to improve EP and achieve organization goals.